THE COMMUNITY SERVICE EDUCATION ABOUT REPRODUCTIVE HEALTH IN YOUTH: PENGABDIAN KEPADA MASYARAKAT PENYULUHAN MENGENAI KESEHATAN REPRODUKSI PADA REMAJA - Rohanah, Rohanah; Sayyidah, Sayyidah (Ruang Ide Publisher, 2022)
Abstract Teenager is a stage between childhood and adulthood. Adolescence, also known as puberty, is a time between childhood and adulthood. In the life cycle of puberty is an important stage in the development of sexuality. Extension is a form of non-formal education effort to individuals or community groups that is carried out in a systematic, planned and directed manner in an effort to change sustainable behavior in order to achieve increased production, income and welfare improvements. The goal is to increase the knowledge of Adolescents there are Information and Challenges of Reproductive Health in Adolescents so that they can behave in a healthy manner. The result of this activity is the high interest and awareness of participants to participate in health education. Increase participants' knowledge about the importance of maintaining healthy reproductive health in adolescence, Increased awareness of participants to empower themselves in healthy adolescent relationships. Keywords: teenager, reproduction, counseling